Assessment of Tidal Energy Resources from Tidal Streams in Sarawak Coastline - A. Q., Jakhrani; A. R. H., Rigit; S. A., Kamboh; W. H., Kong; K. A., Samo (ENCON 2013, 2013)
Tidal energy is one of the most predictable and reliable source of renewable energy. The kinetic energy from tidal streams can be used for generation of electrical power. The purpose of this paper is to assess the extractable tidal energy resources from tidal streams in Sarawak coastline. In order to achieve the objectives, the tidal stream speed and corresponding power densities were computed through empirical equations. The investigation of potential locations was made by weighting of different elements required for the selection of suitable sites. It was found from the analysis that only a single site of Pulau Triso at Batang Lupar fulfilled the minimum required tidal stream speed and the clearance of shallow-draft oceangoing vessels. Off Kuala Igan met only the clearance requirements and the tidal stream speed were lower than set limits. Other examined sites could not fulfil any criterion set for the site selection. It was concluded that Pulau Triso is the only feasible site for the extraction of tidal stream energy among examined locations in Sarawak. However, only shallow-draft oceangoing vessels could pass through the proposed site if the turbines are installed for power generation.